Analysis of Factors Causing Patient Waiting Time in the Emergency Department - I Made Suindrayasa; Hendry Irawan; Meril Valentine Manangkot; I Kadek Saputra (GLOBAL HEALTH SCIENCE GROUP, 2026)
Quality of service in the Emergency Department (ER) of a hospital is required to be fast, effective, and efficient. Overcrowding in the ER must be resolved as quickly as possible to ensure the workload is distributed effectively and the room is not overcrowded with healthcare workers, patients, and their families. Several methods used to alleviate overcrowding in the ER include speeding up/simplifying patient registration, triaging/sorting patients, and shortening patient waiting times by transferring patients to other rooms such as the ward, intensive care unit (ICU), inpatient wards, or other rooms. The purpose of this study was to analyze the factors contributing to patient waiting times in the ER of a hospital in the Bali Province. The factors influencing patient waiting times in the ER include registration time, triage time, consultation time for the attending physician, waiting time for laboratory results, waiting time for radiology results, and waiting time for transfer to the next room. This research method was comparative analytic with a cross-sectional design. The multivariate analysis used was logistic regression. Data collection involved observing factors affecting ER waiting times, with findings recorded on observation sheets. This study employed a purposive sampling technique, involving a total of 98 patients as respondents. Multivariate analysis revealed that the time of patient transfer to the next room was the most dominant factor associated with patient waiting times in the Emergency Department (ER), with an OR of 17.16 at a 95% confidence level. The conclusion of this study is that patient transfer time is a dominant factor affecting waiting times.